Marketing Strategy of Love & Story Design - Šimůnková, Lucie (2020)
This diploma thesis deals with the creation of a marketing strategy for the Love & Story Design brand. The aim of this work was to evaluate the current strategy and improve it. The thesis is divided into two parts. The first part deals with the general marketing strategy for startups and their composition. In the second part of the thesis, a new strategy was set based on the data from the first and research in the form of qualitative and quantitative surveys.